Microwave-assisted synthesis of N-benzylidene-4-fluoroaniline and N-benzylidene-4-Nitroaniline and their inhibitory activities on hCA isoenzymes - Hülya Çelik; Aynur Babagil (International Journal of Secondary Metabolite)
In this study, N-benzylidene-4-fluoroaniline (3a), N-benzylidene-4-nitroaniline (3b) as a result of condensation of benzaldehyde (1) and 4-fluoroaniline (2a), 4-nitroaniline (2b) using a microwave method was synthesized. The structures of the synthesized compounds were characterized by Fouirer Transform İnfrared Spektrofotometre (FTIR spectroscopy), Nuclear Magnetic Resonance (NMR spectroscopy) and elemental analysis methods. The prepared compounds were tested for their inhibitory effects on carbonic anhydrase isoenzymes (hCA-I and hCA-II). The results showed that the synthesized compounds 3a and 3b had a strong inhibitory effect on hCA-I and hCA-II enzymes activity in vitro. By testing these compounds in other CA isoenzymes, more effective CA inhibitors can be formed. Thus, new therapeutic applications can be made for enzyme activators in the near future.